Study of the effects of soiling on PV devices using the spin-coating technique in accelerated indoor exposures. (1st January 2022) - Olivares, D.; Ferrada, P.; Marzo, A.; Pinto, K.; Espinoza, D.; Rabanal-Arabach, J.; Portillo, C.; Fuentealba, E.; Llanos, J.
Graphical abstract: Highlights: We propose a procedure for indoor soiling studies by using spin coating technique. Dust samples were collected from PV modules installed in the Atacama Desert. Homogeneous dust deposition was obtained within 25 s using spin coating technique. Physicochemical characteristics of material allowed understanding the cementation. As dust amount increased, light attenuation in the UV range became more significant. Abstract: Soiling affects the economic profitability of solar photovoltaic plants, reducing productivity of the photovoltaic modules and increasing maintenance costs. Typically, studies on the soiling impact on photovoltaic technologies conducted outdoors require long exposure times. This paper deals with a new methodology for accelerated indoor test. Dust samples from the Atacama Desert are used to study physicochemical aspects of local soiling and its effects in the performance of solar cells. The new methodology is based on spin-coating to deposit homogeneous soiling layers on photovoltaic glass. This technique allows different soil mixtures to be deposited, resulting in the desired surface dust densities. X-ray diffraction and scanning electron microscopy of samples with artificially indoor and naturally outdoor deposited dust revealed similar behavior. In both, gypsum was the soluble material supporting the cementation process. The external quantum efficiency of the solar cell under different soiling conditions allowed to evaluate its effect on the photogenerated current density ( Jph ) for different spectral ranges. As expected from other studies, the influence of soiling is higher in the ultraviolet spectral range than at other wavelengths. It is observed that as the amount of deposited soil increases, the Jph losses are higher in the ultraviolet spectral range than in the visible or infrared. Because of the reduction in current density, efficiency is affected as the surface dust density increases. For instance, the efficiency decreased by 66.5% for 1.37 mg/cm 2 .